2006
DOI: 10.1111/j.1572-0241.2006.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between Weight Gain and Symptoms of Gastroesophageal Reflux in the General Population

Abstract: Weight gain is associated with GERS, independently of BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 23 publications
4
33
0
5
Order By: Relevance
“…However, some gender differences were noted-a weight loss of 5-10% led to a significant reduction in overall GERD scores (P < 0.05) in women; whereas among men, a significant improvement in GERD symptom scores (P < 0.01) was observed after a weight loss of ≥10% of baseline body weight. Similar to this concept, new onset or worsening of pre-existing GERD may occur only after certain threshold weight change as was reported in previous study by Rey et al (39) In that study subjects who gained >5 kg showed three times significantly higher frequency of new onset GERD (39). Although a positive and significant correlation between weight loss and GERD scores was noted, it appears that the correlation is not linear and more complex.…”
Section: Discussionsupporting
confidence: 74%
“…However, some gender differences were noted-a weight loss of 5-10% led to a significant reduction in overall GERD scores (P < 0.05) in women; whereas among men, a significant improvement in GERD symptom scores (P < 0.01) was observed after a weight loss of ≥10% of baseline body weight. Similar to this concept, new onset or worsening of pre-existing GERD may occur only after certain threshold weight change as was reported in previous study by Rey et al (39) In that study subjects who gained >5 kg showed three times significantly higher frequency of new onset GERD (39). Although a positive and significant correlation between weight loss and GERD scores was noted, it appears that the correlation is not linear and more complex.…”
Section: Discussionsupporting
confidence: 74%
“…Weight gain of at least 5 kg, independent of BMI, has been shown to be associated with new or exacerbation of already existing GERD symptoms [12]. In contrast, weight loss has been shown to result in symptom improvement in GERD patients [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…On the contrary, a weight loss amounting to a decrease of BMI of 3.5 kg/m 2 over a period of 14 years decreased the risk of frequent GERD symptoms by nearly 40% (odds ratio, 0.64; 95% confidence interval, 0.42 -0.97) as compared to women without weight loss [4]. In another population-based study in Spain, the subjects with a weight gain over 5 kg coexists with an increased new GERD symptoms (odds ratio, 3.0; 95% confidence interval, 1.6 -6.0) [9]. A hospital-based study found a weight loss of 5-10% in women and > 10% in men, led to a significant reduction in overall GERD symptoms scores [10].…”
Section: Discussionmentioning
confidence: 94%